New Insights into Regulatory T Cells: Exosome- and Non-Coding RNA-Mediated Regulation of Homeostasis and Resident Treg Cells - Li, Peiyao; Liu, Changhong; Yu, Zhibin; Wu, Minghua (Frontiers in Immunology, 2016)
Regulatory T (Treg) cells are a population of cells that are heterogeneous in origin and in functional activity. Treg cells constitute an essential counterbalance to adaptive immune responses. As key regulators of self-tolerance, Treg cells have been implicated in a number of pathologic processes and considered as therapeutic targets. Here, we summarize recent research regarding Treg cell origins and their functional classification, highlight the role of exosomes and non-coding RNA in modulating Treg cell homeostasis, and discuss the current understanding of resident Treg cells.